Digitizing Tribal Law: How Codification Projects such as Tribal Law Online could give New Rise to American Indian Sovereignty - Jacob Franchek (Washington University Law Review, 2017)
“Today, in the United States, we have three types of sovereign entities– the Federal government, the States, and the Indian tribes.” The oft- forgotten American Indian nations have inherent sovereignty to govern themselves, by virtue of their existing as cultural and political entities prior to the founding of the United States. Federally recognized American Indian nations thus have intrinsic authority and jurisdiction over their internal affairs; tribal governments perform executive, judicial, and legislative functions. Despite this fact, most of the federally recognized tribes in the United States have not formally published or codified their laws. What is codified is usually out of date and almost never digitized or published in an online forum. The online databases that do contain tribal laws are “incomplete and are often plagued by broken links, outdated laws, unsearchable documents, and unreadable images.” Accessing these laws and applying them in tribal courts is often very difficult, even for attorneys working for American Indian nations with access to whatever databases exist. Part I of this Note will focus on the ways that Tribal Law Online could be beneficial to American Indian sovereignty. It discusses how codification and digitization will improve Supreme Court recognition of American Indian sovereignty, benefit American Indian nations economically, help them obtain more favorable legislation from Congress, and aid American Indians in shaping their governments to more accurately reflect their cultures. Part II will address potential criticisms of codification and digitization, including fears that allowing nonmembers to codify Oglala law could cause the laws to less accurately reflect Oglala interests, that codification itself could involve the imposition of Anglo-American jurisprudential norms, and that codification could harm existing Oglala customary law. This Note will ultimately conclude that Tribal Law Online and projects like it could potentially advance American Indian sovereignty to a degree heretofore unseen since the founding of the United States.
Keywords: DIGITIZING TRIBAL LAW; American Indian law; Codification; Tribal law; Tribal Law Online